The Use Of Some Statistical Criteria To Show The Role Of Fiscal Policy In Achieving Economic Development In Iraq - Abdulrtha Dagr, Assma; Dhiaa Abdulkareem, Anwaar (Opción, 2019)
The research aims to study the role of financial policies in achieving economic development in Iraq during the period (2004-2017). The research used the descrip- tive approach and the analytical methodology to analyze the study data. The study found that the relationship between government expenditure and GDP growth rate during the period 2004-2017 is not significant. There is a correlation between the government expenditure and the GDP growth rate in Iraq during the study period. This means that it is possible to apply the corrective error correction method. The relationship between the tax rate and the growth rate of GDP during the study period. The correlation between the tax rate and the GDP growth rate in Iraq during the study period, which means the possibility of applying the error correction vector method, the absence of a significant effect of financial policies on economic development In the Iraqi economy during the study period. The study recommended that it is necessary for the Iraqi government to develop more ef- fective financial policies through which to influence the economic development, increase the rates of government spending on sectors that help to achieve economic development quickly while ensuring the continuity of development rates achieved, Changes to the fiscal policy of the Iraqi government to make them more effective, increasing their impact on economic variables that help in achieving real economic development of the Iraqi society and help in achieving the objectives of Iraqi eco- nomic policy, The tax rates imposed on companies and individuals, especially that they did not pay their fruits significantly and work to alleviate the economic burden on individuals and companies in order to encourage them to work and increase production rates, which helps to achieve the required economic development.